Pengaruh Digitasi, Digitalisasi, Transformasi Digital dan Era Digital Terhadap Peningkatan Mutu SDM Pada PT Suraco Jaya Abadi Motor - Iriani, Nisma; Putera, Wahyudi; Hidayah, Rahmat; Agusniati, Andi (Movere Journal, 2024)
The study aims to obtain information about the significance of the influence of digitization, digitalization, digital transformation and the digital era, especially on improving the quality of a company's human resources. This research was conducted at PT. Suraco Jaya Abadi Motor. The population in this study were all active employees of the head office and branch offices of PT Suracojaya Abadi Motor in the South Sulawesi region, be it administrative staff, managers, staff, mechanics to marketing personnel. Meanwhile, the sample obtained was 100 respondents. The sampling technique uses Stratified Random Sampling or stratified random sampling. Data collection techniques through observation, interviews, questionnaires and documentation, while data analysis with multiple regression analysis using SPSS Ver.-23 software. The results of the research findings are digitization, digitalization, digital transformation and the digital era through active employees of the head office and branch offices are able to provide a significant improvement in the quality of human resources of PT Suraco Jaya Abadi Motor.